A política pública municipal de resíduo sólido: sua incidência sobre os catadores de lixo do aterro sanitário do Aurá em Belém - GOMES, Flavia Ferreira (Universidade Federal do Pará, 2013)
This study examines the impact of public policy on municipal solid pickers of recyclable in the landfill of the Aura, in the period 2002 to 2008. The analysis is based on the actions implemented during the administration of “Partido Trabalhista” (PT) 1997-2004 and “Partido Trabalhista Brasileiro” (PTB) 2005… In methodological terms, this is a case study based on review of public policies directed at this population and its organizational forms. The situation of the landfill scavengers of Aura in the town of Belém, is gradually becoming a complex problem to be faced, especially by the municipal government through the implementation of public policies. It is therefore aim of this study to analyze how public policy on solid waste established by the City of Belém, by the Municipal Sanitation (Secretaria Municipal de Saneamento - SESAN), focused on living conditions (employment and political) of the landfill scavengers of Aura. This policy started with the implementation of the Project for Bioremediation. Structured in two main areas of activity one physical and one social. This paper focuses on the analysis of the latter axis, for focused actions for the collectors of recyclable materials, such as representatives of the informal market. The research reveals the strategies of survival, the levels of individual and collective empowerment of the scavengers and the practice of dispensing mediating labor relations and power.